2006
DOI: 10.1089/acm.2006.12.857
|View full text |Cite
|
Sign up to set email alerts
|

The Use of D-Ribose in Chronic Fatigue Syndrome and Fibromyalgia: A Pilot Study

Abstract: D-ribose significantly reduced clinical symptoms in patients suffering from fibromyalgia and chronic fatigue syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 21 publications
2
50
0
2
Order By: Relevance
“…Teitelbaum et al reported a substantial benefit with D-ribose in lessening the pain, discomfort, and mental alteration in patients with fibromyalgia or chronic fatigue syndrome. 9 The two patients with RLS on whom we report also found a benefit with D-ribose, most noted when consumed 3 times a day, similarly to the patients reported in Teitelbaum's study. A controlled cohort study should be performed to further substantiate the findings in this case reports.…”
Section: Discussionsupporting
confidence: 85%
“…Teitelbaum et al reported a substantial benefit with D-ribose in lessening the pain, discomfort, and mental alteration in patients with fibromyalgia or chronic fatigue syndrome. 9 The two patients with RLS on whom we report also found a benefit with D-ribose, most noted when consumed 3 times a day, similarly to the patients reported in Teitelbaum's study. A controlled cohort study should be performed to further substantiate the findings in this case reports.…”
Section: Discussionsupporting
confidence: 85%
“…An open-label uncontrolled pilot study was conducted to determine if d-ribose supplements improved energy-related symptoms in patients with either FM or chronic fatigue syndrome. 40 Patients (N = 41) were given 5 g of d-ribose, twice a day, for a total of 280 g. Two-thirds of the patients experienced significant improvement while receiving the d-ribose, with an average increase in energy of 45% shown on pre-/post-test visual analogue scales (of pain intensity, energy level, sleep quality, and mental clarity), and 30% in global well-being. The treatment was well-tolerated.…”
Section: Diet and Dietary Supplementsmentioning
confidence: 99%
“…An open-label, uncontrolled pilot study evaluated if d-ribose could also improve energy synthesis in patients with CFS and/or FM (N 5 41). 32 Patients were given a twice-daily dose of 5 g of d-ribose for a total of 280 g over a 28-day period. d-Ribose produced significant improvement in * 60% of patients according to pre-and post administration of VAS categories of energy, sleep, mental clarity, pain intensity, and well-being, as well as having an average improvement of 30% in global assessment scoring.…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…40{ According to his study (discussed above in the Dietary Supplements section), he has found d-ribose to benefit his patients. 32 Hormonal support entails testing for and optimizing adrenal, thyroid, testosterone, and estrogen functions. Dr. Teitelbaum considers standard tests (unspecified) to be inadequate for the diagnosis of low hormone levels.…”
Section: Integrative Clinical Approachesmentioning
confidence: 99%
See 1 more Smart Citation